Long-Term Evaluation of the Use of the Transdermal Contraceptive Patch in Adolescents - Stephanie Logsdon; Jessica Richards; Hatim A. Omar (The Scientific World Journal)
The transdermal contraceptive patch, Ortho Evra™, was approved in December 2001 and released on the market in June 2002. In this study, we reviewed clinical data of young women who started the patch between June 2002 and December 2003 in the adolescent medicine clinic at a university-based outpatient center. A total of 62 patients started the patch in that period and two of them were lost to follow-up. Mean age of patients was 17.9 years and mean length of use was 10 cycles. Only 10 patients (16.7%) discontinued use. Reasons for discontinuation were moderate to severe skin irritation (3 patients, 5%), complete detachment (3 patients, 5%), and economic reasons (4 patients, 6.7%). Compliance was excellent overall and the side-effects profile was good. No pregnancies occurred during this period. These results confirmed that the transdermal contraceptive patch is easy to use and an effective method of birth control that may be better tolerated by young women. It also seemed to improve contraceptive compliance in this population.